Determinants of expected performance after ISO 9001 certification withdrawal - Candido, Carlos (2022)
ISO 9001 certification impact on firm performance has been extensively researched. However, despite the high number of firms withdrawing from this certification, the impact of decertification has not received much research attention. This study contributes to filling this gap by analysing the factors that influence the expected performance after decertification (EPAD). The study reviews relevant literature and develops a structural equation model (PLS-SEM) with data from 231 certified organisations. Results reveal that the main factors influencing EPAD are external decertification motivations and internal certification benefits. Internal benefits have a U-shaped relationship with EPAD and external decertification motivations a positive linear relationship. Results show also a negative direct impact of external benefits on EPAD, which is counterbalanced and cancelled by a positive indirect impact from the same variable. Certification barriers and internal decertification motivations have no significant effect. This study is the first to identify and analyse the factors affecting EPAD and, as such, the study findings constitute innovative contributions to the literature. These findings have theoretical and practical implications for (1) the estimation of EPAD, (2) the decision to renew (or not) the certificate, and (3) further suggest that EPAD is a better predictor of decertification than past certification benefits.